Action Research on the Application of Intergenerational Learning Guidance Through Online Curriculum - Cheng, Li-Yuan; Say, Joyce; Chang, Wan-Jing April; Say, Dietermar (Advances in Social Sciences Research Journal, 2023)
Taiwan is at present encountering both low rates of birth and a maturing populace, prompting decreased open doors for intergenerational contact. Chronic diseases, disability, and dementia are all consequences of physical decline with age. This study aims to investigate the impact of intergenerational learning strategies applied to the elderly sports instruction curriculum on instructors in order to improve and alter this situation. Through action research, instructors continuously reflect on and update the elderly sports instruction curriculum to help students design exercise programs that improve students’ stereotypical perceptions of the elderly and promote intergenerational integration by promoting physical and mental health for the elderly. Purposive sampling and action research were used in this study. The subjects of the study were 16 elderly sports instruction curriculum students and one instructor. The primary objective is for students to consider and revise the course material based on elderly feedback. Through triangulation with outside experts, this study will conduct qualitative data analysis. which will also collect feedback and observe how the two generations interact with one another.